LEARNING LOSS AND ALTERNATIVE SOLUTIONS IN PANDEMIC COVID-19 - Indarti Puji Astuti (Madaris: Jurnal Guru Inovatif, 2021)
The purpose of this paper is to examine the impact of the Covid-19 pandemic on the loss of face-to-face learning opportunities and the opportunity to decrease learning outcomes (Learning Loss) at MAN 3 Sleman students. The method used is descriptive with a qualitative approach. Data was collected through structured interviews and questionnaires involving 12 respondents consisting of 6 teachers and 6 students (grades 10, 11 and 12), assisted by various reviews of the existing literature. The results showed that the online learning process at MAN 3 Sleman had an impact on the students’ ability who would experience Learning Loss. Online learning solutions requires independent learning of students and accompanied by cooperation between teachers, homeroom teachers and parents so that students can study remotely. The quality of student learning outcomes can remain awake and avoid learning loss in online learning by preparing curriculum emergency services for students, maximizing learning platforms such as geschool and e-learning madrasah, and evaluating results student learning.